2015
DOI: 10.1117/1.jbo.20.4.048003
|View full text |Cite
|
Sign up to set email alerts
|

In vivoevaluation of battery-operated light-emitting diode-based photodynamic therapy efficacy using tumor volume and biomarker expression as endpoints

Abstract: Abstract. In view of the increase in cancer-related mortality rates in low-to middle-income countries (LMIC), there is an urgent need to develop economical therapies that can be utilized at minimal infrastructure institutions. Photodynamic therapy (PDT), a photochemistry-based treatment modality, offers such a possibility provided that low-cost light sources and photosensitizers are available. In this proof-of-principle study, we focus on adapting the PDT light source to a low-resource setting and compare an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…41 Solid state semiconductor diode lasers provide cost-effective and high power delivery with the advantages of being portable and simple to operate. 42 Light delivery using optical fiber technology can either be directed onto the surface of the lesion using an endoscope or interstitially using multiple fibre-optic catheters implanted percutaneously within solid tumours. 43,44 Photosensitisers used in PDT An ideal photosensitiser should display chemical, photophysical as well as biological characteristics, which allow it to be taken up by tumours, undergo fast clearance and have a large absorption peak at red to near infrared wavelengths where tissue is relatively transparent.…”
Section: Marilena Loizidoumentioning
confidence: 99%
“…41 Solid state semiconductor diode lasers provide cost-effective and high power delivery with the advantages of being portable and simple to operate. 42 Light delivery using optical fiber technology can either be directed onto the surface of the lesion using an endoscope or interstitially using multiple fibre-optic catheters implanted percutaneously within solid tumours. 43,44 Photosensitisers used in PDT An ideal photosensitiser should display chemical, photophysical as well as biological characteristics, which allow it to be taken up by tumours, undergo fast clearance and have a large absorption peak at red to near infrared wavelengths where tissue is relatively transparent.…”
Section: Marilena Loizidoumentioning
confidence: 99%
“…On the other hand, early clinical studies showed that PDT is a safe and effective approach, with remarkable healing and is especially effective for early stage cancerous and precancerous lesions of the oral cavity. While the PDT photosensitizer is readily available, the expensive laser light source that is the current mainstream treatment option is not [10,11].…”
Section: Flexible Qleds For Treatment Of Two Specific Diseases: Diabementioning
confidence: 99%
“…Lasers, despite the advantages mentioned, present a formidable cost per wavelength and require special safety equipment and protocols during use. Additionally, in cases where a direct comparison is possible, researchers have found LEDs and lasers do not differ in their treatment efficacy, 20,[24][25][26][27][28] whereas others have shown LEDs are just as effective as lamps 19,26,28 and more effective than sunlight. 29 Furthermore, LEDs are now widely used to treat many dermatological diseases, 30,31 and a growing body of work suggests LEDs will have a significant role to play in the future of PDT.…”
mentioning
confidence: 99%
“…This may be explained, at least in part, by a lack of competition and limited market size that has discouraged an exciting and robust industry. Those with more specific irradiation requirements, and the appropriate motivation and funding, have reported custom-assembled LED sources for various applications, 27,[36][37][38][39][40] albeit with limited output powers that require tedious experimental protocols. A light source or system that is cost-effective and generalizable to multiple PSs has not yet been reported.…”
mentioning
confidence: 99%